Integrasi Pembibitan Tanaman Tebu Tunas Tunggal dan Budi Daya Ikan Lele - Hidayati Fatchur Rochmah; Restu Puji Mumpuni; Dian Eka Ramadhani (Jurnal Ilmu Pertanian Indonesia, 2021)
This study evaluates the feasibility of integration of the single-bud sugarcane and catfish farming system and the growth rate of both plants and fish. The observation started from September to November 2020. The design used was randomized with one factor. The treatments used were cultivation of single-bud sugarcane in polybags, hydroponic single-bud sugarcane cultivation, integration of single-bud sugarcane-catfish, and catfish cultivation. The results showed that the growth of sugarcane seedlings and the catfish indicate that the integrated cultivation system of sugarcane-catfish is feasible to apply. Such an integration system produces a better number of leaves, stem diameter, leaf area, and root length than the cultivation system of sugarcane seedlings in polybags. The weight of the canopy and the root of sugarcane seedlings in the integration system is also noticeable greater than the sugarcane seedlings cultivated in the polybag. In addition, the rate of catfish growth in the integration system is better than catfish's ordinary cultivation. Keywords: hydroponic, integration farming system, single bud sugarcane planting